The Association of cagA, vacA, babA2, babB and oipA of Helicobacter pylori with Risk of Gastric Carcinoma Development - Zainab H. Alsaadi; Nada Kadlim Hindi; Ali H. Al Marzoqi; Mojtaba Memariani; Maryam Kohansal; Abdolmajid Ghasemian (Fasa University of Medical Sciences, 2022)
Background & Objective: Helicobacter pylori (H. pylori), carried by more than half of the world population, is a major cause of chronic duodenal and gastric ulcers, gastritis and carcinoma. Colonization and toxin production include major virulence traits of H. pylori. The aim of this study was to assess the existence of H. pylori and virulence factors among patients with risk of gastrointestinal carcinoma (GC) in an Iraqi population. Materials & Methods: During May 2016- October 2020 in Babylon, Iraq, a total of 500 biopsy samples were obtained from gastric tissue of patients with GC, gastritis, duodenitis, duodenal ulcer and gastric ulcer and cultured onto the Brucella agar. H. pylori isolates were identified using conventional biochemical and molecular tests. Molecular identification was conducted by amplification of glmM gene using the polymerase chain reaction (PCR) technique. The adhesin (babA2, babB and oipA) and toxin (cagA and vacA) genes were also amplified using PCR technique. Results: Among 500 biopsy samples, 269 (110 from males and 159 from female patients) H. pylori isolates were identified. The age range of patients was 14-69 years (mean age=47.34±7.23). The babA2 and babB genes were detected in 59.47% and 59.10% of isolates, respectively. Notably, babA2 was observed in 89% of GC and 64% of DN strains being significantly more associated with GC and DN (<0.0001 and 0.028, respectively). Furthermore, babB-positive strains were significantly (0.042) more associated with PG. The rate of cagA and vacA was 44.60% and 48.32%, respectively. The cagA was detected in 64.73% of GC, and 100% of PG and DN strains with a significant association. We detected the oipA in 58.36% of strains which was significantly associated with GC (74%, P=0.0001), PG (88%, p<0.0001) and DN (84%, p<0.0001) as compared to oipA-negative strains. Conclusion: The existence of H. pylori babA2, cagA and oipA virulence genes was associated with GC, DN and PG. As these genes play a crucial role in the development of gastric carcinoma, accurate control measure toward hindering the colonization of pathogenic strains is essential.